1985
DOI: 10.1111/j.1600-0528.1985.tb01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Report on caries reduction in French schoolchildren 3 years after the introduction of a preventive program

Abstract: A combination of preventive methods have been used to reduce dental caries in children aged 7-8 at baseline, living in a non-fluoridated area in the West of France. The preventive program involved a daily supervised toothbrushing at school with 180 mg of fluoridated toothpaste, professional prophylaxis every 2 months with topical application of fluoride gel and reinforced motivation. The oral hygiene level was measured using the Silness-Löe plaque index and caries were recorded using the def and DMF surface in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
2
0
5
Order By: Relevance
“…The main study also demonstrated the effi cacy of a daily teacher-supervised toothbrushing programme in which there was no attempt to change the diet, to provide toothpaste and toothbrush for home use [Curnow et al, 2002] or additional professional prophylaxis [Kérébel et al, 1985].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main study also demonstrated the effi cacy of a daily teacher-supervised toothbrushing programme in which there was no attempt to change the diet, to provide toothpaste and toothbrush for home use [Curnow et al, 2002] or additional professional prophylaxis [Kérébel et al, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…Kérébel et al [1985] reported that daily, supervised toothbrushing at school in combination with topical application of fl uoride gel every 2 months signifi cantly reduced dental caries in both the primary and permanent teeth of primary school children. Davies et al [2001] reported that the regular provision of a free toothbrush and toothpaste, containing 1,450 ppm fl uoride, to children initially aged 12 months and living in deprived areas of North West England resulted in a signifi cant reduction (16%) in caries levels when the children were 5-6 years old, compared with a control group that received no such intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Ao contrário do evidenciado em outros estudos, [23][24][25][26][27][28][29][30][31] não foi possível demonstrar um menor risco de desenvolvimento de cárie dentária no grupo de crianças que realizou escovagem de dentes na escola (RR de 0,75; IC 95%: 0,42-1,33), o que pode estar relacionado com o reduzido tamanho do grupo de estudo e com a consequente limitada potência do estudo (b = 0,62).…”
Section: Discussionunclassified
“…5,19,20 Existe, no entanto, evidência da melhoria de comportamentos e redução da cárie dentária com intervenções com pais e crianças que visam a divulgação de conhecimentos de saúde oral [21][22][23] e a supervisão da escovagem em ambiente escolar. [24][25][26][27][28][29][30][31][32] Embora não estejam publicados estudos que demonstrem a efectividade desta estratégia na população portuguesa, ela tem sido recomendada pela Direcção-Geral da Saúde (DGS). No entanto, a prática tem mostrado alguma resistência por parte dos educadores na implementação da escovagem de dentes em meio escolar, 33 pelo que nos parece pertinente avaliar o seu efeito protector, tendo em conta os demais factores que influenciam a saúde oral em Portugal.…”
Section: Re Su Mounclassified
“…Yeni bir yöntem olmamakla beraber, 1960 ve 70'lerde bazı Avrupa ülkelerinde rutin olarak uygulanan 22,23 ve hala Polonya gibi bazı ülkelerde devam ettirilen 20 ; özel bir yöntem, yalnızca florun ağza taşınması açısından değil gecikmiş fırçalama işlemini hatırlatması açısından da önemli bir başlangıç yaratabilmektedir. Ülkemiz gibi diş fırçalama alışkanlığının yaygınlaşmadığı toplumlardaki temel ağız-diş sağlığı koruyucu uygulama felsefesi; temelde mümkün olan en basit ve anlaşılır yöntemle toplumsal bilinci oluşturmaya odaklanmalıdır.…”
Section: Introductionunclassified